Management of brownfield redevelopment by local authority: case study Majlis Daerah Hulu Selangor / Anis Zulfa Johari, Dasimah Omar and Siti Mazwin Kamaruddin - Johari, Anis Zulfa; Omar, Dasimah; Kamaruddin, Siti Mazwin (UiTM Press, 2023)
In Malaysia, the issue of brownfield redevelopment has begun in recent years due to the awareness from various parties to achieve more sustainable development goals. The Town and Country Planning Department, Peninsular Malaysia, Ministry of Local Government Development, address this issue through the existing spatial development policies introduced by formulating the National Urbanization Policy and the National Physical Plan. The Twelve Malaysia Plan emphasises the need to redevelop the brownfield area. Hence, the local authority and related agencies are essential in managing brownfield redevelopment in areas within their jurisdiction. Local authorities must monitor brownfield redevelopment projects through the Structure Plan and Local Plan, besides providing an inventory of brownfield areas (National Physical Planning Framework). Among the significant departments in the Local Authority organisation involved in brownfield redevelopment are the planning, building, environment, and engineering divisions. This study in Lembah Beringin, Hulu Selangor, focuses on officer interviews by giving questionnaires. The researchers made observations to determine the situation in the Lembah Beringin area. At the same time, for the results of the interviews, 14 respondents reflected on their roles and interest in managing, monitoring and controlling land use planning, besides encouraging the private sector to redevelop brownfield areas. Thus, this study highlights some recommendations and strategies for management to realise the desire of Hulu Selangor District Council (HSDC) to establish Lembah Beringin as a viable and sustainable area as the brownfield redevelopment that can create job opportunities for residents and reduce new forest exploration. Redevelopment of brownfield sites can help to reduce development pressure on green land (greenfield), protect environmentally sensitive areas and public spaces and is a valuable resource when correctly planned and efficiently managed.